2016
DOI: 10.5543/tkda.2015.56805
|View full text |Cite
|
Sign up to set email alerts
|

Serum YKL–40/chitinase 3–like protein 1 level is an independent predictor of atherosclerosis development in patients with obstructive sleep apnea syndrome

Abstract: In patients with OSAS, CIMT was increased. This increase was associated with serum YKL-40 level. Increased serum level of YKL-40 may be an early predictor of atherosclerosis development in patients with OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Furthermore, Chi3l1 was found to be secreted from differentiated macrophages in early-stage atherosclerosis lesions 59 , 60 as well as from VSMCs during hyper cholesterol-induced coronary atherosclerotic plaque development in swine 31 . Notably, knockdown of the elevated Chi3l1 expression associated with the atherosclerotic aorta and endothelial dysfunction suppresses the progression of these characteristics in a mouse model 30 - 32 , 34 , 38 , 61 . These data suggest that in addition to its potential role as a circulating biomarker for AD diagnosis 24 - 29 , Chi3l1 might play an important role in vascular inflammation and the development of atherosclerosis in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chi3l1 was found to be secreted from differentiated macrophages in early-stage atherosclerosis lesions 59 , 60 as well as from VSMCs during hyper cholesterol-induced coronary atherosclerotic plaque development in swine 31 . Notably, knockdown of the elevated Chi3l1 expression associated with the atherosclerotic aorta and endothelial dysfunction suppresses the progression of these characteristics in a mouse model 30 - 32 , 34 , 38 , 61 . These data suggest that in addition to its potential role as a circulating biomarker for AD diagnosis 24 - 29 , Chi3l1 might play an important role in vascular inflammation and the development of atherosclerosis in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported elevated YKL-40 levels in different cardiovascular conditions and it has been described a positive association between this marker and mortality [ 10 17 ]. It has been reported an increased YKL-40 expression in patients with carotid atherosclerosis [ 18 ], as well as a positive correlation between common carotid artery intima media thickness (CIMT) and YKL-40 levels in patients with obstructive sleep apnea syndrome [ 16 ] and between arterial stiffness and YKL-40 levels in essential hypertension subjects [ 15 ]. Increased YKL-40 levels have also been found both in patients with T1D and T2D [ 19 22 ], and particularly in T1D and T2D patients with microalbuminuria, suggesting that this glycoprotein might be used as an early marker of vascular disease [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the absence of DLCO elevation could be attributed to the association of two opposite mechanisms occurring during OSAS: (i) an increase in pulmonary capillary blood volume due to obesity and an increase in cardiac output linked to the hyperactivity of the sympathetic system, this latter tends to increase the DLCO; (ii) an alteration of the alveolar-capillary membrane which tends to reduce the DLCO. Indeed, during the course of OSAS in obese patients, an increase in the atherosclerosis and the inflammatory manifestations causing an alteration of the pulmonary exchanger was often noted [14,15,41]. e degree of bronchial inflammation was significantly greater in the OSAS group than the control group.…”
Section: Discussionmentioning
confidence: 99%